2002
DOI: 10.1046/j.1440-1746.2003.02920.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment of hepatic function: Utility of a new convenient two‐compartment model analysis using galactosyl human serum albumin scintigraphy

Abstract: These results suggest that this new compartment analysis will be useful in evaluating liver function, as it is accurate, simple and convenient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…liver uptake, uniformity of hepatic uptake, hepatic left lobe to right lobe ratio, spleen uptake and volume) and Child-Pugh score, indocyanine green test or other classifications of liver disease severity [156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174]. Successful radiotracers were Technetium-99 m (99m-Tc) sulfur colloid, 99m-Tc-phytate colloid and 99m-Tc diethylenetriamine pentaacetic acidgalactosyl human serum albumin.…”
Section: Single Photon Emission Computed Tomography (Spect)mentioning
confidence: 99%
“…liver uptake, uniformity of hepatic uptake, hepatic left lobe to right lobe ratio, spleen uptake and volume) and Child-Pugh score, indocyanine green test or other classifications of liver disease severity [156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174]. Successful radiotracers were Technetium-99 m (99m-Tc) sulfur colloid, 99m-Tc-phytate colloid and 99m-Tc diethylenetriamine pentaacetic acidgalactosyl human serum albumin.…”
Section: Single Photon Emission Computed Tomography (Spect)mentioning
confidence: 99%
“…Many investigators have reported that some measurements obtained from 99m Tc-GSA liver scintigraphy are strongly correlated with previously identifi ed indicators of hepatic function and that they are useful for assessing hepatic function. [8][9][10][11][12] We found that HH15 and LHL15 levels mildly correlated with preoperative ICGR15 and serum ChE, which may imply that the 99m Tc-GSA measurements indicate a capacity of protein synthesis or bilirubin excretion that differs from the capacity obtained by the evaluation of liver transaminases. The 99m Tc-GSA value could be a simple method of predicting postoperative liver dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…They have been confi rmed clinically as useful measures of hepatic function; therefore, 99m Tc-GSA scintigraphy has been recognized as the best method for assessing liver functional reserve, [8][9][10][11][12] achieving results comparable with those obtained by liver biopsy. HH15 represents the retention of the tracer in the blood, and LHL15 illustrates the hepatic uptake of the tracer from the blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations